ALK-Positive Anaplastic Large Cell Lymphoma: A Diagnostic Dilemma for the Otolaryngologist in a Resource Poor Setting - Nicholas Figaro (Hindawi Limited, 2021)
Anaplastic large cell lymphoma is a rare subtype of non-Hodgkin’s lymphoma. The morphological diversity with which its anaplastic cells confer make the diagnosis of this hematological entity extremely challenging to the pathologist in a resource poor setting. We present a case of a 35-year-old male with a nasopharyngeal mass and cervical lymphadenopathy and the adversities faced by out otolaryngology department with obtaining the diagnosis of ALK-positive anaplastic large cell lymphoma.